211k views
1 vote
Steps for solving 3x + 18 = 54 are shown.

Explain how Step 1 helps solve the equation.
3x + 18 = 54
3x + 18 - 18 = 54 - 18

Original equation
Step 1
Step 2
Step 3
Step 4

User Webie
by
6.0k points

2 Answers

3 votes

Answer:

Step 1 allows to remove term "18" from the left member of the equation.

Explanation:

3x + 18 = 54

3x + 18 - 18 = 54 - 18 (as we can see 18-18=0)

3x + 0 = 54 - 18

3x = 54 - 18

term "18" was remove.

User Costique
by
4.9k points
5 votes

Answer:

It contributes to the isolation of the variable

Explanation:

The Step 1 is


3x+18=54\\3x+18-18=54-18

Now, the step one helps to solve the equation because we need to isolate the variable, taking all the terms to the other side of the equality, and the first step is moving the term 18 to the other side. So, it contributes to the isolation of the variable, which is mandatory.

User Hlt
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.